Penguatan Perilaku Hidup Bersih Dan Sehat Melalui Pendidikan Jasmani Di Sd Negeri Cilengkrang - Hanum Assyifa Putri; Qory Maryam An Naba; Rio Adrian; Tania Rizky Salsabila; Adang Sudrazat (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Clean and Healthy Living Behavior (PHBS) is crucial for the development of children in elementary school, but its adoption in rural regions encounters numerous challenges. This is evident in Cilengkrang Village, located in Wado Sub-district, Sumedang Regency, where there is a shortage of proper waste disposal systems and limited health education available for children. The purpose of this community service project was to enhance the awareness and abilities of second and third graders at SD Negeri Cilengkrang regarding PHBS using a Physical Education framework. The program included educating students about PHBS, showing them how to wash their hands with soap, teaching them the right way to brush their teeth, and engaging them in group exercise activities. The approach taken involved interactive and enjoyable learning sessions that paired informative guidance with practical demonstrations and hands-on experience, using straightforward teaching tools. The outcomes demonstrated that the students grasped and could apply the correct methods for handwashing and toothbrushing, while also showing great enthusiasm for physical exercises. This initiative highlights that merging Physical Education with health advocacy is an effective way to instill habits of cleanliness and health in young children, presenting a promising model for ongoing interventions in elementary schools within rural locations.